The state of online audio qur'an and its public perception - Abubakar, Adamu; Zeki, Akram M.; Hisham, Akmal; Mahmud, Murni; Chiroma, Haruna; Hirawan, Tutut (Design for Scientific Renaissance, 2014)
The Qur’an has become widely accessible in the internet and is available in audio, text and animated video format. However, the uncertain credibility of most of these online sources makes it hard for users to ascertain the authenticity of the Qur’anic text as appearing on screen. The need to first establish the authenticity of the Qur’anic text as presented on the web justifies a detailed examination of the phenomenon of online audio Qur’an and the way its reliability and usefulness is perceived by users. This study uses quantitative survey research methodology and investigates the state of online audio Qur'an and its perceived impact. The research findings indicate that “trust” and “accuracy” exerts a huge impact on positive perception of the source and content of online audio Qur'an. However, the effect of accuracy and trust on the content and sources of online audio Qur’an are perceived differently whereas the perception of the quality of content of online audio Qur’an is common. Also, the majority of users remain skeptical of the credibility of most of the sources of online Qur’an in almost all formats.